POTENSI TUMBUHAN CIPLUKAN (Physalis angulata Linn.) SEBAGAI ANTIOKSIDAN ALAMI - Nuranda, Apri; Saleh, Chairul; Yusuf, Bohari (Jurusan Kimia FMIPA UNMUL, 2016)
Potential of Ciplukan plant as natural antioxidants, the aim of this research is to determine the antioxidant potential of Ciplukan plant. First step is to know the active compound of the plant. Alkaloid and saponin are present at ciplukan leaves, stem and fruit, meanwhile steroid is present at leaves and stem. Moreover, flavonoid and triterpenoid is only present at stem and fruit, respectively. Phytochemical test are employed to dermine the active compound in the leaves, stem and fruit of ciplukan. Brine shimp lethality test are conducted to determine toxicity of the extract.The LC50 from the leaves extract is 962.054 ppm, stem extract is 753.558 ppm and at the fruit is 1.004,73 ppm. Antioxidant activity measurement conducted by reacting the sample with 1,1-difenil-2-pikrilhidrazil radical and measures the absorbance at wavelength 517 nm. Vitamin C is use as positive control. The inhibition concentration 50 vitamin C is 34.91 ppm. Meanwhile, the Inhibition concentration 50 of the leaves extract is 60.34 ppm, the stem extract is 56.36 ppm and the fruit extract is 63.46 ppm. These result indicated that Ciplukan plant is potensial as antioxidant source.Keywords: leaves, stems, fruit ciplukan (Physalis angulata.L), antioxidants,, DPPH and BSLT.